2017
DOI: 10.1177/0363546517712231
|View full text |Cite
|
Sign up to set email alerts
|

Double-Bundle Versus Single-Bundle Anterior Cruciate Ligament Reconstruction: A Prospective Randomized Study With 10-Year Results

Abstract: Double-bundle ACL reconstruction resulted in significantly fewer graft failures than single-bundle ACL reconstruction during the follow-up. Knee stability and OA rates were similar at 10 years. The most severe OA changes were found in the patients who had the longest delay from the primary injury to ACL reconstruction and in the patients who underwent partial meniscal resection at the time of ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 47 publications
9
123
0
2
Order By: Relevance
“…Patellofemoral joint OA after ACL reconstruction has been mostly unrecognized. 17,18 In recent studies, Yoon et al 19 and Jarvela et al 3 showed that the reconstruction technique has only a small effect on OA progression, so our finding is in line with the previous finding. We also found that ACL reconstruction has little effect on contralateral patellofemoral joint OA progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patellofemoral joint OA after ACL reconstruction has been mostly unrecognized. 17,18 In recent studies, Yoon et al 19 and Jarvela et al 3 showed that the reconstruction technique has only a small effect on OA progression, so our finding is in line with the previous finding. We also found that ACL reconstruction has little effect on contralateral patellofemoral joint OA progression.…”
Section: Discussionsupporting
confidence: 91%
“…3,9 Table 5 shows that revision ACL reconstruction due to complete tear of ACL graft was higher in group DB than in group SB, while revision ACL reconstruction due to instability was higher in group SB than in group DB. This is in accordance with many recent papers 3,[20][21][22] that the patients who undergo DB ACL reconstruction may have some advantages in knee kinematics. Because the two grafts cross each other inside the joint, acting separately at different knee angles, they mimic the normal ACL anatomy more closely than a single graft.…”
mentioning
confidence: 99%
“…8 Therefore, the current trend in anterior cruciate ligament reconstruction techniques has shifted to the anatomical double-bundle reconstruction, which involves reconstruction of both anteromedial bundle and posterolateral bundle of anterior cruciate ligament, with reported improved clinical outcomes. 10,11 Although its long-term efficacy remains controversial, the rationale of double-bundle anterior cruciate ligament reconstruction has been supported by the research data of various functional anatomical and biomechanical studies. [12][13][14][15] The canine CrCL is also composed of two bundles, the cranial part and caudal part, [16][17][18][19] like in humans.…”
Section: Introductionmentioning
confidence: 99%
“…and SB ACL reconstruction. 18 However, 18 trials (69%) reported significantly better results with the DB technique than with the SB technique. In this study, 145 papers from 2008 to date compared the two techniques of SB and DB ACL reconstruction, and similar mid-and long-term outcomes were achieved with the SB and the DB techniques, as demonstrated by the good to optimal results in both patient groups by Mayr et al 19 However, rotational stability is a problem after ACL reconstruction 20 which has motivated surgeons to find a solution to this problem and it has been shown that the ALL on the lateral compartment of the knee is necessary for the stabilization of the rotational laxity.…”
Section: Discussionmentioning
confidence: 98%